Influence of Osmolarity and the Presence of an Osmoprotectant on Lactococcus lactis Growth and Bacteriocin Production - Uguen, Patricia (American Society for Microbiology, 1999)
Growth inhibition of Lactococcus lactis provoked by increasing osmolarity is reversed when glycine betaine (GB) or its analogs are added to a defined medium. Lacticin 481 production increased sharply with growth medium osmolarity in the absence of osmoprotectant but remained unaffected when GB was supplied in media of increasing osmolarity.